EVALUATION OF GENETIK PURITY ON 20 GENOTYPES OF BAMBARA GROUNDNUT (Vigna subterranea L. Verdcourt) SELECTED FROM SINGLE SEED DESCENT MORPHOLOGICAL CHARACTERS - Arif, Ainin; Kendarini, Niken; Kuswanto, Kuswanto (Produksi Tanaman, 2016)
Bambara groundnut (Vigna subterranea L. Verdcourt) is a leguminous plant that originate from African and has been cultivated in others Countries. In Indonesia, especially in â€‹â€‹Bogor (West Java), it is known as â€œKacang Bogorâ€, while in Gresik (East Java) it is known as â€œKacang Kapriâ€. Important issue in development of Bambara Groundnut local lines was a genetic diversity, so that they need to be purified in order to develop a new variety or as a parent crosses. This research was conducted in research station of Agricultural Faculty, Brawijaya University, in Jatikerto Village, Malang Regency on May until September 2014 and using single plant method so the observation was due to all individual plant. Material in this research was 20 genotypes of bambara groundnut by single seed descent. The result showed five population in genotypes CCC 1.4.1, SS 2.2.2, GSG 1.5, BBL 10.1 and CCC 1.1.1 have each a similarity coefficient more than 0,80 and 15 genotypes had a similarity coefficient less than 0,80, it can be continued with the second selection of Single Seed Descent. The character of days of first flowering and harvest age in 20 genotype had a low variability, while in number of flower character, number of pods per plant and fruit set, it had a low, medium and high variability. Genotype BBL 10.1 and GSG 1.5 have a similarity coefficient more than 0,80 and have potential on yield components which is based on early maturity, high number of pods per plant and high fruit set.